Pediatric Cardiology in The Past, Present, and Future: Its Role in The Prevention and Management of Cardiovascular Disease - Bambang Madiyono (Indonesian Pediatric Society, 1998)
Â The title mentioned above is chosen in a consideration that we are now entering the Second Stage Long-Term Development Plan (or PJP-II), even the Sixth Five-Year Development Plan is being passed in part. This is a stage of quality and productivity improvement of our human resources for the sake of developmental success to achieve a fair and wealthy society based on the Pancasila and the Constitution of 1945. In his presidential speech before the General Meeting of People's Advisory Assembly or MPR on Friday, Aug. 16, 1996, President Soeharto declared that: